Tongue exercise ameliorates structural and functional upper airway deficits in a rodent model of hypoglossal motor neuron loss - Keilholz, Amy N.; Pathak, Ishan; Smith, Catherine L.; Osman, Kate L.; Smith, Lauren; Oti, Grace; Golzy, Mojgan; Ma, Lixin; Lever, Teresa E.; Nichols, Nicole L. (Frontiers in Neurology, 2024)
Tongue weakness and atrophy can lead to deficits in the vital functions of breathing and swallowing in patients with motor neuron diseases (MNDs; e.g., amyotrophic lateral sclerosis (ALS) and pseudobulbar palsy), often resulting in aspiration pneumonia, respiratory failure, and death. Available treatments for patients with MNDs are largely palliative; thus, there is a critical need for therapies targeting preservation of upper airway function and suggesting a role for tongue exercise in patients with MNDs. Here, we leveraged our inducible rodent model of hypoglossal (XII) motor neuron degeneration to investigate the effects of a strength endurance tongue exercise program on upper airway structure and function. Our model was created through intralingual injection of cholera toxin B conjugated to saporin (CTB-SAP) into the genioglossus muscle of the tongue to induce targeted death of XII motor neurons. Rats in this study were allocated to 4 experimental groups that received intralingual injection of either CTB-SAP or unconjugated CTB + SAP (i.e., control) +/-tongue exercise. Following tongue exercise exposure, we evaluated the effect on respiratory function (via plethysmography), macrostructure [via magnetic resonance imaging (MRI) of the upper airway and tongue], and ultrafine structure [via ex vivo magnetic resonance spectroscopy (MRS) of the tongue] with a focus on lipid profiles. Results showed that sham exercise-treated CTB-SAP rats have evidence of upper airway restriction (i.e., reduced airflow) and structural changes present in the upper airway (i.e., airway compression) when compared to CTB-SAP + exercise rats and control rats +/-tongue exercise, which was ameliorated with tongue exercise. Additionally, CTB-SAP + sham exercise rats have evidence of increased lipid expression in the tongue consistent with previously observed tongue hypertrophy when compared to CTB-SAP + exercise rats or control rats +/-tongue exercise. These findings provide further evidence that a strength endurance tongue exercise program may be a viable therapeutic treatment option in patients with XII motor neuron degeneration in MNDs such as ALS. Future directions will focus on investigating the underlying mechanism responsible for tongue exercise-induced plasticity in the hypoglossal-tongue axis, particularly inflammatory associated factors such as BDNF.